THANKSGIVING TABLE, A CULINARY PERFORMANCE - Sondakh, Sonya Indriati; Yoesoef, M. (UI Scholars Hub, 2023)
In Minahasa, North Sulawesi, the people in the villages of Minahasa has an annual harvest-related celebration called Pengucapan Syukur or Thanksgiving celebration of the people of Minahasa. According to a research in South Minahasa, this Christian celebration that has been practiced at least since 1940 has gone through changes along the way. This tradition has developed as such in line with the dynamics of the Minahasans. Thanksgiving used to be celebrated only in the villages in some parts of Minahasa, but nowadays this tradition has also been celebrated in the capital city of Minahasa, Manado. This local thanksgiving tradition clearly focuses on the food being served on the thanksgiving table. In this celebration they have to serve abundant food of traditional taste, championing nasi jaha and dodol. Each and every household has special budget that allows them to prepare abundant food for this occasion. This is a qualitative research using ethnographic approach. Schechner’s performance theory is used to understand the meaning of the thanksgiving table.